Community Service Activities: Socialization of Financial Literacy for Micro, Small and Medium Enterprises Between Two Countries in the Motamasin Border Area - Nay, Yustina Alfira; Timuneno, Antonius Y.W.; Betu, Kristina Wada; Moi, Maria Odriana Veronica; Malut, Maria Goreti; Baso, Purnamasari; Brito, Manuel; Jesus, Monica Pareira De (Asian Journal of Community Services, 2024)
The aim of this activity is to provide outreach to the public about simple financial recording for MSMEs. Providing knowledge to the public about financial planning and management. Providing knowledge to the public regarding the preparation of Financial Reports for MSMEs. The theories of empowerment, training and financial literacy are adapted in this article to explain the financial literacy of MSMEs in cross-border regions. Financial literacy services include needs surveys, program planning, interactive training, discussions, effectiveness evaluations, and continued development through partnerships. The results is The MSME community in Border Areas knows about Simple Financial Recording; The Border Area MSME community knows about Financial Planning and Management for MSMEs; The MSME community in Border Areas knows about the preparation of financial reports